2008
DOI: 10.1007/978-0-387-78952-1_20
|View full text |Cite
|
Sign up to set email alerts
|

Compstatin: A Complement Inhibitor on its Way to Clinical Application

Abstract: Therapeutic modulation of the human complement system is considered a promising approach for treating a number of pathological conditions. Owing to its central position in the cascade, component C3 is a particularly attractive target for complement-specific drugs. Compstatin, a cyclic tridecapeptide, which was originally discovered from phage-display libraries, is a highly potent and selective C3 inhibitor that demonstrated clinical potential in a series of experimental models. A combination of chemical, bioph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
167
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(169 citation statements)
references
References 68 publications
(71 reference statements)
0
167
0
2
Order By: Relevance
“…At almost every step of all three pathways, there is crosstalk with proteins from other physiological pathways. 5,21 The alternative pathway is continuously activated by spontaneous hydrolysis of the internal thioester bond in C3 to form C3(H 2 0) ( Figure 1). This molecule, although not cleaved, can fulfil the same role as C3b in a C3 convertase.…”
Section: The Complement Cascadesmentioning
confidence: 99%
See 1 more Smart Citation
“…At almost every step of all three pathways, there is crosstalk with proteins from other physiological pathways. 5,21 The alternative pathway is continuously activated by spontaneous hydrolysis of the internal thioester bond in C3 to form C3(H 2 0) ( Figure 1). This molecule, although not cleaved, can fulfil the same role as C3b in a C3 convertase.…”
Section: The Complement Cascadesmentioning
confidence: 99%
“…Compstatin has been developed as a potential treatment that targets the complement system. 21 It is a peptide that is administered by intra-vitreal injection, and which binds to C3 protein and inhibits binding of the C3 molecule to the C3b in the C3 convertase. The injected material forms a gel that slowly releases the molecule over many months, therefore dosing intervals could be relatively long.…”
Section: Treatmentsmentioning
confidence: 99%
“…Therefore, compstatin is an ideal compound to inhibit classical, lectin as well as AP activation. 61 It has been tested in several animal models and shown to be an effective complement inhibitor. 62,63 Recently, Risitano and co-workers elegantly demonstrated that pegylated compstatin not only efficiently prevents lysis of PNH-RBCs, but also C3 deposition.…”
mentioning
confidence: 99%
“…In addition, a neutralising C5 antibody utilizing a different epitope to Eculizumab has also been developed known as 'Mubodina' however sepsis and the development of inflammatory disease are side effects that have limited clinical trials [134]. In contrast, Compstatin is a cyclic tridecapeptide C3 inhibitor function that continues to be promising in clinical trials as a treatment for age-related macular degeneration [135]. It binds C3 reversibly whilst inhibiting the convertase mediated cleavage of C3 to C3a and C3b affecting the classical and alternative pathways.…”
Section: Target -Systemic Complementmentioning
confidence: 99%
“…Anti-MASP-2 is a human monoclonal antibody that selectively inhibits MASP-2 thereby blocking the lectin pathway. There are ongoing clinical trials in aHUS and if successful this selective blockade may be associated with a lower infectious risk as the classical pathway would remain unaffected [135]. Previous murine models have shown a reduction in IR injury of the myocardium and gastrointestinal tract with blockade of MASP-2 [51].…”
Section: Target -Systemic Complementmentioning
confidence: 99%